2015
DOI: 10.1097/aci.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Current screening approaches for antibody deficiency

Abstract: There is a strong case for the use of calculated globulin in screening for antibody deficiency. Further work is required to integrate laboratory results with clinical data to reduce diagnostic delay in patients with hitherto unsuspected antibody deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…IgG, IgA and/or IgM) below the reference range for age [10,11]. In line with these reports, a recent review concluded that low IgE levels should be considered as a clinical laboratory 'flag' to screen for antibody deficiency [12]. Some of these studies, however, may have been biased, as they correlated only immunoglobulin levels that had been measured for unspecified clinical reasons.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…IgG, IgA and/or IgM) below the reference range for age [10,11]. In line with these reports, a recent review concluded that low IgE levels should be considered as a clinical laboratory 'flag' to screen for antibody deficiency [12]. Some of these studies, however, may have been biased, as they correlated only immunoglobulin levels that had been measured for unspecified clinical reasons.…”
Section: Introductionmentioning
confidence: 65%
“…Patients with antibody deficiencies are often diagnosed with a significant delay [12,25]. This may be partly because the health-care professionals involved in evaluating these patients are unaware of this differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable ones include: (i) hypergammaglobulinemia should prompt the consideration of HIV infection, especially if greater than 30 g/L, (ii) low-background optical density on the IgA TTG assay or low-background staining on antiendomysial IgA testing should lead to the suspicion of IgA deficiency, (iii) very low IgE (<2 IU) when testing for allergy should make clinicians check the other immunoglobulins, as approximately 7% of those patients may have an antibody deficiency, (iv) patients with low-globulin gap should undergo a follow-up measurement of IgG concentration as 89% of patient with a globulin gap <18 g/L had an IgG <6 g/L. Prompt use of the globulin gap has been shown to improve early detection of hypogammaglobulinemia [11,12], (v) low monocyte counts have been associated with a recently described PID caused by GATA-2 deficiency, and (iv) idiopathic thrombocytopenic purpura can be the presenting feature of primary or secondary immune deficiencies.…”
Section: Screeningmentioning
confidence: 99%
“…This group of proteins is a valuable serum biomarker for several pathologies that affect directly or have repercussions in the immune system. For instance, decreased levels of IgG may be associated with primary antibody deficiency, protein-losing enteropathies, nephrotic syndrome, or iatrogenic hypogammaglobulinemia as a consequence of immunosuppressant, anti-convulsant, or cytotoxic therapies [3][4][5][6][7]. The level of serum IgG is also a valuable predictor for the risk of infection in transplant recipients [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The level of serum IgG is also a valuable predictor for the risk of infection in transplant recipients [8][9][10]. Moreover, high IgG levels are indicators of autoimmunity (e.g., demyelinating diseases, lupus erythematosus), chronic infection, liver diseases (e.g., autoimmune hepatitis), and lymphoproliferative disorders (e.g., multiple myeloma) [3,[11][12][13][14]. The early diagnosis of these conditions is a key factor to minimize the risk of permanent organ damage and to proceed with adequate therapy, accounting for less morbidity and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%